Penerjemahan Uslub al-Hazf dalam Terjemahan Al-Qur’an Berbahasa Indonesia - Zakiyatun Najwa; Khobirul Amru; Nor Fatihah Izzati (SUHUF, 2026)
This article investigates the application of uṣlub al-hazf in two Indonesian Qur’anic translations, namely the 2019 Revised Edition of Al-Qur’an dan Terjemahannya (the Qur'an and its Translation) compiled by the Ministry of Religion Affairs (MoRA) and Al-Qur’an dan Maknanya (the Qur'an and its Meaning) by Quraish Shihab. Both works represent different strategies for rendering Arabic expressions into Indonesian, which in turn affect translation problems and readers’ comprehension of Qur’anic meaning. This study employs a qualitative approach with a library research method, using the two translations as primary sources and analyzing them through the perspectives of balagah and translation theory. The findings identify two major translation models in dealing with al-hazf: (1) accommodation of omission, and (2) non-accommodation of omission. Overall, Quraish Shihab’s translation (Al-Qur’an dan Maknanya) is found to be more responsive to the rhetorical dimensions of balagah, particularly in preserving al-hazf, than the 2019 Ministry translation (Al-Qur’an dan Terjemahannya). These differing strategies influence meaning construction, interpretive orientation, and readers’ engagement with the religious message, indicating that successful translation requires rhetorical as well as semantic sensitivity.